Is there a role of surgical resection for uveal malignant melanoma liver metastases: report of two cases - Oğuzhan Şal; Emre Adalier; Görkem Uzunyolcu; Celal Caner Ercan; Semih Çakır; Neslihan Berker; Melek Büyük; Beslen Göksoy; Feza Ekiz; Kürşat Rahmi Serin (Egyptian Liver Journal)
Abstract Ocular malignant melanoma (OMM) is a rare, aggressive eye cancer, and liver metastasis is the most important prognostic factor. Despite advances in local and systemic therapies for liver metastasis, the 5-year survival rate is less than 20%. This report presents two cases of OMM with liver metastases. Case 1 was a 65-year-old male who had liver metastasis at the 2nd year of the eye treatment and underwent after. Heexperienced recurrent liver metastasis 1 year after surgery and died at the 38th month of diagnosis; this highlights the aggressive nature of metastatic OMM and limitations of current treatments. Case 2 was a 63-year-old female who underwent laparoscopic metastasectomy in the 2nd year of the primary treatment. No recurrences were observed after the 6th month of the liver resection, and long-term monitoring was planned. These cases underscore the variable progression of OMM liver metastases, which may present indolently but remain challenging to treat. Unlike cutaneous melanoma (CMM), liver metastases in OMM may offer opportunities for surgical resection and prolonged survival, emphasizing the need for tailored therapies, vigilant surveillance, and further research into novel treatments.